First total synthesis of hoshinoamide A - Zhou, Haipin; Rui, Zihan; Yang, Yiming; Xu, Shengtao; Shao, Yutian; Liu, Long (Beilstein Journal of Organic Chemistry, 2021)
Hoshinoamides A, B and C, linear lipopeptides, were isolated from the marine cyanobacterium Caldora penicillata, with potent antiplasmodial activity against chloroquine-sensitive Plasmodium falciparum. Herein, we describe the first total synthesis of hoshinoamide A by the combination of liquid-phase and solid-phase peptide synthesis. Liquid-phase synthesis is to improve the coupling yield of ʟ-Val3 and N-Me-ᴅ-Phe2. Connecting other amino acids efficiency and convergence is achieved by solid-state synthesis. Our synthetic strategy could synthesize the target peptide in high yield with good purity
Keywords: antimalarial; highly methylated polypeptides; hoshinoamides; total synthesis

(untitled) - Cowman, A. F.; Healer, J.; Marapana, D.; Marsh, K. (Cell, 2016)

World malaria report 2020 (World Health Organization, 2020)

(untitled) - Singh, S. K.; Singh, S. (Int. J. Pharm. Sci. Rev. Res., 2014)

(untitled) - Achan, J.; Talisuna, A. O.; Erhart, A.; Yeka, A.; Tibenderana, J. K.; Baliraine, F. N.; Rosenthal, P. J.; D'Alessandro, U. (Malar. J., 2011)

(untitled) - Kumar, S.; Bhardwaj, T. R.; Prasad, D. N.; Singh, R. K. (Biomed. Pharmacother., 2018)

(untitled) - Golenser, J.; Waknine, J. H.; Krugliak, M.; Hunt, N. H.; Grau, G. E. (Int. J. Parasitol., 2006)

(untitled) - Hsu, E. (Trans. R. Soc. Trop. Med. Hyg., 2006)

(untitled) - Devine, S. M.; Challis, M. P.; Kigotho, J. K.; Siddiqui, G.; De Paoli, A.; MacRaild, C. A.; Avery, V. M.; Creek, D. J.; Norton, R. S.; Scammells, P. J. (Eur. J. Med. Chem., 2021)

(untitled) - Shibeshi, M. A.; Kifle, Z. D.; Atnafie, S. A. (Infect. Drug Resist., 2020)

(untitled) - Ojha, P. K.; Kumar, V.; Roy, J.; Roy, K. (Expert Opin. Drug Discovery, 2021)

(untitled) - Iwasaki, A.; Tadenuma, T.; Sumimoto, S.; Shiota, I.; Matsubara, T.; Saito-Nakano, Y.; Nozaki, T.; Sato, T.; Suenaga, K. (J. Nat. Prod., 2018)

(untitled) - Iwasaki, A.; Ohtomo, K.; Kurisawa, N.; Shiota, I.; Rahmawati, Y.; Jeelani, G.; Nozaki, T.; Suenaga, K. (J. Nat. Prod., 2021)

(untitled) - Zong, Y.; Sun, X.; Gao, H.; Meyer, K. J.; Lewis, K.; Rao, Y. (J. Med. Chem., 2018)

(untitled) - Bu, X.; Xie, G.; Law, C. W.; Guo, Z. (Tetrahedron Lett., 2002)

(untitled) - Dunetz, J. R.; Magano, J.; Weisenburger, G. A. (Org. Process Res. Dev., 2016)

(untitled) - Li, Y.; Manickam, G.; Ghoshal, A.; Subramaniam, P. (Synth. Commun., 2006)

(untitled) - Liu, L.; Wu, S.; Wang, Q.; Zhang, M.; Wang, B.; He, G.; Chen, G. (Org. Chem. Front., 2018)

(untitled) - Guo, W.; Li, J.; Fan, N.; Wu, W.; Zhou, P.; Xia, C. (Synth. Commun., 2005)